The Clinical Sociology Honours Programme at the University of KwaZulu-Natal (UKZN) in South Africa - Mariam Seedat-Khan; Jayanathan Govender (Clinical Sociology Review)
A qualification in Clinical and Applied Sociology facilitates initiatives to  mitigate and reduce pervasive social problems prioritising women, children, migrants, families and society. Graduate studies in Clinical and Applied Sociology is limited in South Africa and the global South, therefore a postgraduate degree focused on applying interdisciplinary perspectives in diverse social contexts was initiated. This approach addresses social problems, policies, and enhances community well-being through direct intervention, research, and advocacy. Graduates gain competencies in healthcare, community organizations, government agencies, and educational institutions, contributing to societal change and development. The Clinical Sociology postgraduate programme at the University of KwaZulu-Natal produces change agents by designing and implementing clinical and applied models and interventions. Post-graduates augment critical skills, proficiencies and dexterities by combining research academic interests and societal needs. The aim of the programme typically involves applying l theories and methods to analyse and intervene in social issues and problems at the individual, community, and societal levels. The programme focuses on understanding human behaviour in a social context, diagnosing social problems, and developing strategies for social change. It prepares students for roles in policy development, social research, community work, and advocacy, aiming to promote social justice and improving quality of life. The Bachelor of Social Science in Clinical and Applied Sociology (Honours) is open to students in possession of an undergraduate Sociology qualification or a cognate discipline. A qualification in Clinical Sociology facilitates initiatives that seek to  mitigate and reduce pervasive social problems in the interest of women, children, migrants, families and society.